Gestational diabetes mellitus. Experience at Hospital Militar Central - Ylave Morales, Guillermo (2015)
Objective: To determine the incidence, risk factors and complications of gestational diabetes mellitus (GDM). Design: Observational, analytical, transversal type, retrospective study. Setting: Hospital Militar Central Luis Arias Schreiber, Lima, Peru, a teaching hospital. Participants: Pregnant women with gestational diabetes mellitus. Interventions: We identified all new cases of GDM between 2000 and 2005 in order to evaluate risks associated to known predisposing factors and frequency distribution. Main outcome measures: Incidence, risk factors and complications of GDM. Results: Among the 602 pregnant women with suspicion of GDM who delivered during the study period, 4,75% (86 cases) had GDM, with clear increasing linear tendency (p <0,05). GDM associated risk factors were family history of DM and/or GDM (aOR =18,4, CI95%: 10,7-31,7; p<0,001), BMI >25 kg/m2 (aOR =1,78, CI95%: 1,11-2,84; p =0,0161), history of newborn with macrosomia (aOR =1,78, CI95%: 1,11-2,84; p=0,0161) and personal history of DM and/or DMG (aOR =4,58, CI95%: 1,56-12,6; p=0,0028); whereas DMG was associated with increased risk of dystocia (aOR =3,41, CI95%: 1,41-8,24; p =0,0116), fetal macrosomia (aOR =2,78, CI95%: 1,56-4,96; p =0,0010), preeclampsia (aOR =2,77, CI95%: 1,42-5,40; p =0,0050) and hypoglicemia in the newborn (aOR =72,8, CI95%: 16,5-321,2; p<0,0001). Conclusions: GDM incidence during the study period was 4,75% and independently associated to BMI >25 kg/m2, family history of DM and/or DMG, personal history of DM and/or CDM or of a child with macrosomia, and significant increased risk of dystocia, fetal macrosomia, preeclampsia and hypoglycemia in the newborn.